2012
DOI: 10.4049/jimmunol.1201521
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan Curdlan Induces IL-10–Producing CD4+ T Cells and Inhibits Allergic Airway Inflammation

Abstract: A number of studies have suggested a correlation between a decreased incidence in infectious diseases and an increased incidence of allergic diseases, including asthma. Although several pathogen-derived products have been shown to possess therapeutic potential for allergic diseases, it remains largely unknown whether β-glucan, a cell wall component of a variety of fungi, yeasts, and bacteria, has a regulatory potential for allergic diseases. In this study, we examined the effect of curdlan, a linear β-(1-3)-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…As suggested earlier, the ability of glycans to directly drive alternative activation of APCs may lie in the nature of the glycans. The majority of the studies demonstrating that glycans by themselves activate and mature APCs into anti-inflammatory and Th2-driving phenotypes employed multivalent neoglycoconjugates or naturally occurring ␤-glucans (9,60,61). The results presented here showing that LNFPIII-NGC are taken up and processed via the classical endosomal pathway suggest that signaling originating from endosomes may be the requisite intracellular signaling pathways that multivalent glycans activate to initiate APC polarization to anti-inflammatory and/or Th2-type cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As suggested earlier, the ability of glycans to directly drive alternative activation of APCs may lie in the nature of the glycans. The majority of the studies demonstrating that glycans by themselves activate and mature APCs into anti-inflammatory and Th2-driving phenotypes employed multivalent neoglycoconjugates or naturally occurring ␤-glucans (9,60,61). The results presented here showing that LNFPIII-NGC are taken up and processed via the classical endosomal pathway suggest that signaling originating from endosomes may be the requisite intracellular signaling pathways that multivalent glycans activate to initiate APC polarization to anti-inflammatory and/or Th2-type cells.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, we and others demonstrated that glycans found on pathogens in human milk and in certain foods are capable of inducing alternative activation of APCs (9)(10)(11). Glycans on glycoproteins and glycolipids are known to play important roles not only for binding of glycoproteins to receptors on APCs but also in increasing phagocytosis (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…14 The ability of intraperitoneally injected BG to modulate allergic airway inflammation through IL-10-secreting CD4 T cells has been demonstrated recently. 15 We also noted that the numbers of IL-10-positive CD4 T cells in draining LNs and the secretion of IL-10 in the in vitro T cell assay significantly increased after topical BG application. Microbial infection or inflammatory mediators stimulate the secretion of inflammatory cytokines, such as IL-17, TGF-b, or IL-27, from antigenpresenting cells that promote the generation of IL-10-producing T cells.…”
Section: Discussionmentioning
confidence: 87%
“…15,22,26,27 Kearley et al 28 reported that CD4þCD25þ T cells can suppress the Th2 cell-driven response of airway inflammation to allergens in vivo by an IL-10-dependent mechanism. In our data, we observed that BG application induced an increase in the population of Foxp3þ CD4þ CD25þ Treg cells in the draining LNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation